Effect of para-aminobenzoic acid on morphologic changes of the retina in the rd10 mouse model of retinitis pigmentosa - Galbinur T. (Oftalʹmologiâ, 2014)
Purpose: Histological evaluation of the influence of PABA on the course of retinal degeneration and the state of outer nuclear layer (ONL) of the retina in rd10 mice. Methods: the present experiment studied PR model in rd10 mice (Jackson Labs, Maine, USA) homozygous for a recessive mutation in the b-subunit of rod phosphodiesterase. Animals in the treatment group (n = 28) were intraperitoneally injected with PABA in saline (50 mg/kg) 6 times a week from the third day after birth till 4.5 weeks of age. Animals in the control group (n = 24) were intraperitoneally injected with saline using the same protocol. At 3 and 4.5 weeks of age, eyes were enucleated. After fixation and dehydration, the samples were placed in paraffin and serial sections, 4 microns sick, were obtained through the center of the optic nerve. thickness of ONL and the number of rows of photoreceptor nuclei in the ONL of central, middle and peripheral parts of the retina were analyzed to access the morphological condition of retina. t-test was used to compare the dif- ference between two groups (p ≤ 0.05, unpaired two-tailed t-test). Results: At the age of three weeks, the thickness of ONL and the number of rows of photoreceptor nuclei in the ONL is reducing more than twofold in both experimental groups compared with healthy mice group. there is a tendency toward greater thickness of the ONL and the greater number of rows of nuclei in the central zone and mid-peripheral retina at the age of three weeks in the group of animals that were injected with PABA compared to the control group. At the age of 4.5 weeks both the thickness of the ONL, and the number of rows of photoreceptor nuclei in the ONL were significantly greater in the peripheral retina of the animals in the treatment group compared with the control group (p <0.05). Conclusion: Systemic administration of PABA has a stabilizing effect on the degenaration process of ONL of the retina in rd10 mice. thus, PABA, with its good safety profile can be an effective addition to the antioxidant therapy of retinitis pigmentosa.